2022
DOI: 10.1108/bij-11-2020-0605
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the synergy between R&D and advertising and firm performance: a neural network approach

Abstract: PurposeThis paper explores the nonlinear interactions of research and development (R&D) and advertising and their synergistic effect on firm performance using Tobin's Q. This study also aims to investigate differential synergy patterns under varying levels of exports with a precision impact on performance.Design/methodology/approachUnlike a conventional statistical approach, this study uniquely presents a neural network approach to explore the dynamic interplay of strategic factors. A multilayer perceptron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“…In contrast to the research that suggests that R&D and advertising have conflicting effects, another stream of research has reported that there is a complementary relationship in the joint employment of R&D and advertising (Burciu et al, 2020;Kwon et al, 2022b;Peng et al, 2018). For example, Peng et al (2018), in their investigation of the synergistic effect of the simultaneous deployment of R&D and advertising, use a sample of 317 firms across 27 industry sectors and find that R&D and advertising have a positive interaction, with a significant interaction effect, thereby further supporting the contention that the proper allocation of joint resources has a positive influence on value creation.…”
Section: Interplay Of Advertising Intensity and Randd Intensitymentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast to the research that suggests that R&D and advertising have conflicting effects, another stream of research has reported that there is a complementary relationship in the joint employment of R&D and advertising (Burciu et al, 2020;Kwon et al, 2022b;Peng et al, 2018). For example, Peng et al (2018), in their investigation of the synergistic effect of the simultaneous deployment of R&D and advertising, use a sample of 317 firms across 27 industry sectors and find that R&D and advertising have a positive interaction, with a significant interaction effect, thereby further supporting the contention that the proper allocation of joint resources has a positive influence on value creation.…”
Section: Interplay Of Advertising Intensity and Randd Intensitymentioning
confidence: 99%
“…From a methodological perspective, efficiency analysis using an optimization method such as data envelopment analysis (DEA) (Ayabakan et al, 2017;Yu et al, 2018) has been widely used; BIJ however, a lack of predictive power and sensitivity to outliers have been noted as the method's shortcomings. To address such drawbacks, researchers have recently deployed nonparametric machine learning techniques such as MLP (Kwon et al, 2018(Kwon et al, , 2022bMolinos-Senante and Maziotis, 2022). In this pioneering study, we follow Dutta et al's (2005) conceptualization of firm capabilities and adopt the approach taken by Kwon et al (2018Kwon et al ( , 2022a in operationalizing capabilities and subsequent segmentations.…”
Section: Interplay Of Randd Advertising and Exportsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study by (Airout et al, 2023), there is an influence of advertising expenditure on financial performance. (Kwon et al, 2022) discovered that advertising generates promising aspects for improving innovation and marketing performance, which directly impacts financial performance. Therefore, the following hypothesis is proposed:…”
Section: Hypothesis Developmentmentioning
confidence: 99%